River engineering for flooding characteristics in the upper-stream part of Bengawan Solo Sub-watershed. Issue 1 (January 2021) - Syaifurahman, A; Nurzain, D A; Prastica, R M S
Abstract: Flooding in Surakarta, which is located in the upper-stream part of Bengawan Solo Sub-watershed, needs further investigation to reduce the disaster impact. This study conducted a flood analysis in the sub-watershed to find out how much the impact of flooding on the river flow that has the risk of flooding due to the overflow of water and extreme weather. The research aims to investigate the hydraulic characteristics of the river in the sub-watershed towards the flooding and identifies the river engineering strategy for mitigation. Based on the results of the hydrological and hydraulics analysis, the existing channel was flooded due to being unable to accommodate the return flood discharge, so a new channel design was needed. The design of new channels is done by widening and being able to deepen the channel. The result of the analysis of the new channel indicates that the capacity could accommodate a discharge capacity of 8915.93 m 3 /second with its river bank safety factor value of 3.14. In conclusion, river engineering compromises good strategy for flood mitigation in the study area.